Structural integrity assessment for a component of the bucket-wheel excavator. Issue 2 (13th May 2014) - Cernescu, Anghel; Marsavina, Liviu; Dumitru, Ion
Abstract : Purpose: – The purpose of this paper is to present a methodology for assessing the structural integrity of a tie member from a bucket-wheel excavator, ESRC 470 model, which was in operation for about 20 years. The tie member is made of S355J2N structural steel. Following the period of operation, the occurrence of microcracks which can propagate by fatigue is almost inevitable. It is therefore necessary to analyze the structural integrity and the remaining life of the component analyzed. Design/methodology/approach: – In principle, the assessment methodology is based on three steps: first, the evaluation of mechanical properties of the material component; second, a BEM analysis using FRANC 3D software package to estimate the evolution of the stress intensity factor based on crack length and applied stress; third, risk factor estimation and remaining fatigue life predictions based on failure assessment diagram and fatigue damage tolerance concept. Findings: – Following the evaluation procedure were made predictions of failure risk factor and remaining fatigue life function of crack length and variable stress range, for a high level of confidence. Originality/value: – As results of this analysis was implemented a program for verification and inspection of the tie member for the loading state and development of small cracks during operation.